MAPK modulation of yeast pheromone signaling output and the role of phosphorylation sites in the scaffold protein Ste5 - Winters, Matthew J. (Mol Biol Cell, 2019)
Mitogen-activated protein kinases (MAPKs) mediate numerous eukaryotic signaling responses. They also can modulate their own signaling output via positive or negative feedback loops. In the yeast pheromone response pathway, the MAPK Fus3 triggers negative feedback that dampens its own activity. One target of this feedback is Ste5, a scaffold protein that promotes Fus3 activation. Binding of Fus3 to a docking motif (D motif) in Ste5 causes signal dampening, which was proposed to involve a central cluster of phosphorylation sites in Ste5. Here, we reanalyzed the role of these central sites. Contrary to prior claims, phosphorylation-mimicking mutations at these sites did not impair signaling. Also, the hyperactive signaling previously observed when these sites were mutated to nonphosphorylatable residues arose from their replacement with valine residues and was not observed with other substitutes. Instead, a cluster of N-terminal sites in Ste5, not the central sites, is required for the rapid dampening of initial responses. Further results suggest that the role of the Fus3 D motif is most simply explained by a tethering effect that promotes Ste5 phosphorylation, rather than an allosteric effect proposed to regulate Fus3 activity. These findings substantially revise our understanding of how MAPK feedback attenuates scaffold-mediated signaling in this model pathway.